(untitled) (Research, Society and Development, 2021)
With the advancement of forensic science, the involvement of Legal Dentistry in the success of human identification became noticeable. Objective: To carry out an integrative literature review on the main anatomical aspects for human identification in Forensic Dentistry. Methodology: This is an integrative literature review, whose search was carried out at the Virtual Health Library (VHL). The descriptors "Anatomy" and "Legal Dentistry" were used, with the assistance of the Boolean operator "and", initially obtaining 178 results. The eligibility criteria were as follows: articles published in English, Portuguese and Spanish; publications between January 2015 and March 2021; articles that suit the theme. Results and Discussion: All selected articles had an objective related to human identification. Most studies sought to analyze methods for estimating age and sexual dimorphism (45%, n = 10). The anatomical structures most cited in the articles evaluated were palatal wrinkles (36.4%, n = 8). Such results can be corroborated through the word cloud formed through the analysis of the articles, where it is observed that the most mentioned words were respectively palatal wrinkles, analyze, estimate, age, forensic identification and sexual dimorphism. The Similitude Analysis shows four main nuclei of words, to quote: “palatal wrinkles”, “estimate”, “analyze” and “sexual dimorphism”. Final Considerations: There is a prevalence of several anatomical features present in the stomatognathic system, which are fundamental for forensic research in human identification. The results of this review answered the guiding question established in the methodology.